Bioinformatics Analysis Reveals miR-98-5p as a potential Inhibitor of Tumor cell proliferation and metastasis in Colorectal Cancer by targeting the FZD3 receptor of the Wnt signaling pathway - Kenneth, Mutebi John (Brac University, 2022)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2021.